Do Subnational Fiscal Rules Reduce Public Investment? The Case of Fiscal Responsibility Laws in India. (May 2023) - Pathak, Rahul
This article examines whether the adoption of deficit targets by subnational governments in India influenced the composition of public spending. Using dynamic panel estimations, this study finds that the adoption of fiscal responsibility laws (FRLs) by Indian states is correlated with improvements in their budget balances, but the same period also witnessed significant cuts in development spending. Furthermore, the states have reduced their capital expenditure and social sector spending after adopting FRLs, while the increases in tax and nontax revenues are insignificant. The subnational governments in developing countries that are adopting numerical deficit and debt targets should explore mechanisms to minimize the distortionary impacts of fiscal targets on the composition of subnational spending since reduced expenditure on development and capital projects may be counterproductive for fiscal sustainability in the long run as these expenditures tend to have significant positive externalities.